2002
DOI: 10.1136/gut.50.4.530
|View full text |Cite
|
Sign up to set email alerts
|

Detection of epithelial tumour RNA in the plasma of colon cancer patients is associated with advanced stages and circulating tumour cells

Abstract: Background: Although circulating tumour DNA has been detected in patients with different types of cancer, little is known of free RNA in cancer patients. Aims: We investigated the presence of RNA from epithelial tumours in plasma from patients with colorectal carcinomas, and its correlation with tumour characteristics and circulating tumour cells. Methods: β-actin mRNA was analysed to assess the viability of plasma RNA in samples from 53 patients with colonic cancer and 25 controls. Subsequently, nested primer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
110
1
8

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(127 citation statements)
references
References 29 publications
8
110
1
8
Order By: Relevance
“…In breast cancer exRNAs have been documented by a number of research groups [63,[96][97][98]. We present the most documented studies on cell-free exRNAs and CTC associated RNAs.…”
Section: Extracellular Rnas and Ctcs Associated Rnas In Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…In breast cancer exRNAs have been documented by a number of research groups [63,[96][97][98]. We present the most documented studies on cell-free exRNAs and CTC associated RNAs.…”
Section: Extracellular Rnas and Ctcs Associated Rnas In Breast Cancermentioning
confidence: 99%
“…Initially, Silva et al [96] identified CK19 mRNA in plasma of breast cancer patients (49%) in comparison to healthy controls (20%). On evaluation of clinicopathological parameters (including patient age, tumor size, histopathological type and stage, lymph node metastases, ER and PR status, proliferative index) with molecular data, two parameters (tumor size and proliferative index as determined by Ki-67 IHC) were associated with the presence of plasma CK19 mRNA.…”
Section: Cytokeratin 19mentioning
confidence: 99%
“…One area of intense breast cancer research has been in assessing prognostic factors of patient outcomes, and several molecular markers have been evaluated in association with established histologic and clinical prognostic parameters of breast cancer (Honkoop et al, 1998;Rizzieri et al, 1999;Sabbatini et al, 2000;Silva et al, 2001).…”
mentioning
confidence: 99%
“…The detection of epithelial tumour RNA in plasma from colon cancer patients is associated with advanced stages and circulating tumour cells (Silva et al, 2002). Two different studies regarding patients with head and neck squamous cell carcinoma (HNSCC) and OSCC, respectively, found that serum p53 antibody is a significant prognostic factor for nodal metastasis (Chow et al, 2001;Hofele et al, 2002).…”
Section: Discussionmentioning
confidence: 99%